1973
DOI: 10.1042/cs0450313
|View full text |Cite
|
Sign up to set email alerts
|

The Lipids and Lipoproteins of Human Peripheral Lymph, with Observations on the Transport of Cholesterol from Plasma and Tissues into Lymph

Abstract: 1. The lipids and lipoproteins of lymph obtained from the dorsum of the foot were examined in seven human subjects. 2. The concentration of total cholesterol in lymph was about one-tenth that in plasma and was significantly correlated with the plasma total cholesterol concentration. The ratio of esterified to total cholesterol in lymph was similar to that in plasma. 3. Triglyceride was detectable in lymph, but the concentration was less than one-tenth that in plasma and was unrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 8 publications
5
53
0
Order By: Relevance
“…[3][4][5]36 Second, LCAT activity, which catalyzes the conversion of pre-␤ HDLs to CE-rich ␣ HDLs, 4,5 appears to be very low in tissue fluid. 37,38 We have confirmed that human lymph has an extremely low cholesterol esterification rate in vitro (M.N.N. et al, unpublished data, 1999).…”
Section: Nanjee Et Al Lymph Apoa-i-containing Particlessupporting
confidence: 51%
“…[3][4][5]36 Second, LCAT activity, which catalyzes the conversion of pre-␤ HDLs to CE-rich ␣ HDLs, 4,5 appears to be very low in tissue fluid. 37,38 We have confirmed that human lymph has an extremely low cholesterol esterification rate in vitro (M.N.N. et al, unpublished data, 1999).…”
Section: Nanjee Et Al Lymph Apoa-i-containing Particlessupporting
confidence: 51%
“…Fractions were eluted in 0.4 ml of the same buffer, and the radioactivity of each fraction was determined using liquid scintillation counting. The void volume (V 0 ) of the columns was determined by the elution profile of [ 3 H]DNA, while the total volume (V t ) was determined by the elution profile of free 35 SO 4 (28).…”
Section: Characterization Of Proteoglycansmentioning
confidence: 99%
“…The remaining medium for each condition was combined with the protease inhibitors benzamidine-HCl (Sigma, 5 mM), 6-aminocaproic acid (Sigma, 100 mM), and PMSF (Sigma, 50 mM) prior to purification. 35 S-labeled proteoglycans were purified from the harvested media using ion-exchange chromatography (23). Media samples containing radiolabeled proteoglycans were applied to DEAESephacel minicolumns equilibrated in urea buffer [8 M urea, 2 mM EDTA, 50 mM Tris-HCl, and 0.5% Triton X-100 (pH 7.5)].…”
Section: Measures Of Cell Growth and Cytotoxicitymentioning
confidence: 99%
“…4 In the skin, as in other extrahepatic tissues, the concentration of LDL is much lower (only 1/10) than in the corresponding blood plasma. 40 Thus, in the skin, mast cell activation leads to a rapid increase of LDL concentration in the extracellular fluid and so creates conditions suitable for the binding of LDL to exocytosed heparin proteoglycans. 4 By blocking this increase, a mast cell-stabilizing drug would have an additional benefit in preventing mast cell-dependent foam cell formation in the skin.…”
Section: Discussionmentioning
confidence: 99%